Lithospheric structures of the eastern Himalayas as revealed by receiver function analysis - Xiang, Bo; Xu, Xiao; Tong, Xiaofei; Wu, Jiajie; Li, Chunsen; Yu, Jiahao; Luo, Xucong; Guo, Xiaoyu (Frontiers in Earth Science, 2023)
Although the Himalayan-Tibetan orogen is a result of compressional tectonics, the orogen also hosts active rifts accommodating east-west extension orthogonal to the north-south India-Asia convergence. In this study we address the question of how the north-trending rifts were formed by conducting high-resolution seismic imaging survey across southeastern Tibet where the Cona rift is exposed. Our work shows that the crustal structures of this youngest rift in southern Tibet was constructed by multiple-scale structures that are decoupled with depth and long rift trend. We suggest this deformation style to have resulted from eastward extrusion of the middle and upper crust with increasing speeds to the north towards the Yarlunbg-Zangpo suture. The differential eastward extrusion in turn may have contributed to the formation and evolution of the eastern Himalayan syntaxis.